Traduzir o mundo vivido : a metafísica da linguagem de Walter Benjamin - Dal Forno, Ricardo Lavalhos (2012)
The emergence of philosophical projects can be observed in German Philosophy in the last years, which address the issue of the alternatives to the philosophy in the context of the crisis in the concept of self-awareness . Among those positions that are born of the crisis of philosophy subjectivities is the language theory of Walter Benjamin. In this dissertation, the concept of lived world aims to talk about something that is presented as a founder philosophical act. It refers to a previous space and ante predicative from which the things take its place and start their movements in human experience. In Walter Benjamin this condition of being previous to the world is essentially linguistic. And that is why we speak of a translation of this world already always assumed. The philosopher makes it clear that part of the theoretical framework of transcendental philosophy of Kent, but, however, already points to overcome this way of thinking when it shows that the subjectivity does not determine the sense of the being, but experiments and participates in it. In this way of thinking has been central the fact of the language, the sense and the history to be the a priori with which man operate its world. Thus passes the mediation categorical of the experience objects by subjectivity to a language as medial of all knowledge. And then the model of conscious philosophy must be substituted by the model of language philosophy. However, the language does not emerge here just as the natural human language, but as the universal instance of expression of all things, and thus coextensive to the world. The language, as a totality, appears in human thoughts, in their comprehensions, in their desires, in their landscapes and provides the text that the human knowledge seeks to be the translation in nominating speech. And with this, the epistemic authority moves from a subject that represents the world for a variety of linguistic interests of subjects nominators. Thus, the theory of Walter Benjamin, the man is no longer just "donor" and the meaning becomes too "participant" in the sense of the world